Consumer Market and Consumer Behavior - Risman Nugraha (FEB Universitas Maritim Semarang, 2023)
In this era of globalization, marketing is more of an information warfare between different parties with the aim of making sales. The marketing environment is rapidly changing, and with these changes, the need for information, latest products, shifts in buyer attitudes and behaviors towards decision-making and product acquisition, as well as the ability to identify opportunities in appropriate marketing, becomes essential. This paper is a literature review using a qualitative descriptive approach, aiming to describe product mix strategies. The methodology employed for data collection is documentation, along with various articles and books, followed by content analysis. The findings of this paper reveal that studying consumers can provide insights for the development of new products, product uniqueness, pricing, distribution channels, advertising messages, and other new marketing elements. A focal point for understanding behavior is the stimulus-response model. Buyer characteristics and decision-making processes lead to specific buyer decisions. The marketing task involves comprehending what occurs in the buyer’s consciousness from external stimuli to the emergence of the buyer's purchasing decision.